Gerakan Literasi Di Kalangan Mahasiswa Sebagai Pengaruh Pembelajaran Daring (Online) - Muslim, Ibnu Fiqhan; Salsabila, Fahmi (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2021)
The purpose of this study was to determine the effect of literacy activities, obstacles and efforts made by students in carrying out and completing assignments from teachers.  This research is a qualitative descriptive study.  The subjects in the study are Unindra students of the Economic Education Study Program. Data collection techniques through interviews, observation and documentation.  Students conduct online teaching and learning activities due to the impact of the Covid-19 pandemic. These conditions make students have to be able to be more independent to move actively by maximizing literacy activities so that the learning process runs optimally. Give assignments to find their own material from various book titles or the internBased on the results of the study, it can be seen that 1) literacy activities give additional insight to students, 2) students need guidance from the teacher to determine the books to read or journal to read, to complete the material that has been made, 3) the teacher must evaluate the material made by including the source, and 4  ) students will have broad knowledge and good competence with alot of reading sources they have read